A5RE4X[TO4]4 crystal growth and photoluminescence. Fluoride flux synthesis of sodium and potassium rare earth silicate oxyfluorides1. Issue 25 (7th July 2015) - Latshaw, Allison M.; Wilkins, Branford O.; Hughey, Kendall D.; Yeon, Jeongho; Williams, Derek E.; Tran, T. Thao; Halasyamani, P. Shiv; zur Loye, Hans-Conrad
<x xml:space="preserve">Abstract</x> Crystals of Na5RE4F[SiO4]4 (RE = Pr, Nd, Sm–Tm) and K5Pr4F[SiO4]4 were grown by flux growth. Antiferromagnetic ordering, second harmonic generation, intense optical properties, and fluorescence quantum yield are discussed.